The Effectiveness of Hurdle Drill and Shadow Exercises to Improve Footwork Skills in Badminton - Indra Ferdiansyah Kurniawan; Ayi Suherman; Respaty Mulyanto (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2024)
This research shows the importance of this type of exercise in badminton to improve footwork skills. The research aimed to determine the effect of hurdle drills and shadow training on footwork and which exercises are the most effective. This research uses a quantitative approach method with a quasi-experimental design. The sample involved in this study consisted of 30 PB athletes. Sampurna Sumedang, aged 10-14, was selected using purposive sampling techniques. This study involved three groups; One control group was a conventional exercise, and two experimental groups were doing hurdle drills and shadow exercises. Pretest and posttest data were obtained using Tohar's badminton footwork research instrument. Data processing and analysis using ANAVA: Sig. value 0.03 < α = 0.05, meaning significant differences from each group to footwork. The post hoc test showed the results of a hurdle drill with a value of 15.30, shadow training with a result of 14.70, and a control group with a value of 13.60. In conclusion, hurdle drill training, shadow training, and conventional training are effective in badminton footwork. The results of this study show that hurdle drill exercises are better than shadow exercises and conventional exercises because they are more varied and efficient.